Determinants of Financial Performance on Firm Value in Textile and Garment Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) - Cicilia Erly Istia; Adawiyah, Nida Nusaibatul; Mufid Suryani; Ayunda Rizky Amalia (HM Publisher, 2023)
Stock investment is an investment that is considered exclusive for investors. One thing that needs to be known when investing is price-to-book value. The importance of price to book value for investors is the urgency of this study. This study aimed to analyze the factors that can influence Price to Book Value. This study is a quantitative study, using secondary data from textile and garment companies listed on the Indonesia stock exchange for the 2018-2021 period. A total of 8 companies were included in this study. Data were analyzed using multiple linear regression. The results of this study indicate that partially the return on assets and total asset turnover variables have no significant effect on the price book value, while the current ratio and debt to equity ratio have a significant effect on the price to book value. But simultaneously, return on assets, total asset turnover, current ratio, and debt to equity ratio have a significant effect on price to book value.